2020
DOI: 10.1177/0954405420976661
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of compressed air assisted-turning-burnishing process for improving machining quality, energy reduction and cost-effectiveness

Abstract: The burnishing process is used to enhance the machining quality via improving the surface finish, surface hardness, wear-resistance, fatigue, and corrosion resistance, and it is mostly used in aerospace, biomedical, and automotive industries to improve reliability and performance of the component. The combined turning and burnishing process is therefore considered as an effective solution to enhance both machining quality and productivity. However, the trade-off analysis between energy consumption, surface cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Furthermore, the combination of turning and burnishing processes is confirmed to be feasibility for improving surface quality, energy reduction, and cost-effectiveness. 12,13 In addition to significantly reducing roughness, the results also indicated that the energy consumption and production cost could be decreased by 20.15% and 17.19%.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the combination of turning and burnishing processes is confirmed to be feasibility for improving surface quality, energy reduction, and cost-effectiveness. 12,13 In addition to significantly reducing roughness, the results also indicated that the energy consumption and production cost could be decreased by 20.15% and 17.19%.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, the combination of turning and burnishing processes is confirmed to be feasibility for improving surface quality, energy reduction, and cost-effectiveness. 12,13 In addition to significantly reducing roughness, the results also indicated that the energy consumption and production cost could be decreased by 20.15% and 17.19%. In recent years, ultrasonic-assisted burnishing (UB) has developed rapidly and has been widely used in the field of surface modification because of the formation of deep compressive residual stress and surface work hardening, and decrease of surface roughness. Hence, the high-quality and high-efficient machining of the laser cladded layers is prone to be achieved with the combination of turning and UB treatment.…”
Section: Introductionmentioning
confidence: 98%
“…In earlier studies of the ball burnishing process, the Taguchi method [43][44][45][46][47][48][49][50] and response surface methodology (RSM) [51][52][53][54][55][56] were widely used. The Taguchi method reduces the number of experiments required for analysis but considers only the main effects on the process and does not allow consideration of the interaction between the input variables.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease environmental impacts and obtain sustainable manufacturing, the energy consumed and carbon emissions should be minimized for the rotary turning operation. 21,22 The empirical models of the average roughness, turning forces, and cutting temperature for various ADRT processes have been proposed in the previous publications. Unfortunately, the comprehensive models of the total specific energy and carbon emission have not been developed.…”
Section: Introductionmentioning
confidence: 99%